2016
DOI: 10.1051/epjconf/201611108002
|View full text |Cite
|
Sign up to set email alerts
|

233U mass yield measurements around and within the symmetry region with the ILL Lohengrin spectrometer

Abstract: Abstract. The study of fission yields has a major impact on the characterization and understanding of the fission process and is mandatory for reactor applications. The LPSC in collaboration with ILL and CEA has developed a measurement program on fission fragment distributions at the Lohengrin spectrometer of the ILL, with a special focus on the masses constituting the heavy peak. We will present in this paper our measurement of the very low fission yields in the symmetry mass region and the heavy mass wing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The local odd-even effect [13] give some information on the pairs breaking but also on the neutron emission process. An experimental program on isomeric ratios (IRs) measurements was developed since 2012 [19]. Especially a focus on the evolution of IR as function of fission product kinetic energy was made [20,21].…”
Section: Other Observables Of Interest To Study the Fission Processmentioning
confidence: 99%
“…The local odd-even effect [13] give some information on the pairs breaking but also on the neutron emission process. An experimental program on isomeric ratios (IRs) measurements was developed since 2012 [19]. Especially a focus on the evolution of IR as function of fission product kinetic energy was made [20,21].…”
Section: Other Observables Of Interest To Study the Fission Processmentioning
confidence: 99%
“…The ND2016 difference in the descent to the symmetry region seems to be coming from the appearance of a tail at low kinetic energy. It has been shown that this component is the consequence of a change of the fission fragment ionic charge due to their collision with the LOHENGRIN residual gas [9,11]. In order to remove this undesired component, an indicator of contamination as well as a procedure to correct the kinetic energy were developed [9,11].…”
Section: Experimental Sidementioning
confidence: 99%
“…It has been shown that this component is the consequence of a change of the fission fragment ionic charge due to their collision with the LOHENGRIN residual gas [9,11]. In order to remove this undesired component, an indicator of contamination as well as a procedure to correct the kinetic energy were developed [9,11]. Nevertheless this component still persists and simple generalisation tends to confirm the consistency of these structures [9,11].…”
Section: Experimental Sidementioning
confidence: 99%
See 1 more Smart Citation